Evaluasi Pelatihan Tenaga Kerja oleh Dinas Tenaga Kerja Kota Batam Tahun 2021 - Purba , Ana Lamtiar; Nazaki; Adiputra, Yudhanto Satyagraha (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2023)
The main objective of this program is to increase the absorption of labor in the world of work, reduce unemployment and increase the skills of participants. This study aims to evaluate workforce training by the Batam City Manpower Office in 2021 limited to Tourism HRD training only The research method used. methods and uses data collection techniques in the form of observation, interviews, and documentation The results of the study show that the evaluation of the implementation of the Tourism HRD training program in Batam City in 2021 is considered feasible to continue, but there are some improvements. This can be seen based on the Input Indicator found problems with incomplete facilities. From the Process Indicator experienced problems during the registration administration process. From the output indicators as a whole, it has been implemented well, increased knowledge and skills of the training participants and received certificates. From the Impact Indicator there is a problem of not having an effect on participating in HRD Tourism workforce training in 2021 for participants who have no tourism background at all so it is just as difficult before attending the training to be absorbed in the world of work, it is necessary to monitor and collect data by the Batam City Manpower Office after the participant completes the job training program.